2018
DOI: 10.2116/analsci.18p422
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Inorganic Anions and Cations in Water and Biological Samples by Capillary Electrophoresis with a Capacitive Coupled Contactless Conductivity Detector Using Capillary Filling Method

Abstract: An analytical method for concurrent analysis of inorganic anions and cations has been developed using a capillary electrophoresis (CE)-capacitively coupled contactless conductivity detector (C 4 D) system. Although hydrodynamic and electrokinetic injection techniques have been widely used in CE, we employed a capillary filling method (CFM) for the analysis of inorganic ions. The procedure is relatively simple and has the advantage that CMF does not require pressure control and vial exchange. Three anions (chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In order to move the cations towards the detector and prevent them from exiting the capillary at the injection end, a hydrodynamic flow towards the detector end was superimposed. In the capillary filling method, the separation capillary is filled with a sample containing anions and cations dissolved in BGE, and after a high voltage application, the anions and cations move to the appropriate electrode, based on their mobilities under conditions with suppressed EOF [85]. The analytes form boundaries and migrate towards the C 4 D detector.…”
Section: Simultaneous Determination Of Anions and Cationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to move the cations towards the detector and prevent them from exiting the capillary at the injection end, a hydrodynamic flow towards the detector end was superimposed. In the capillary filling method, the separation capillary is filled with a sample containing anions and cations dissolved in BGE, and after a high voltage application, the anions and cations move to the appropriate electrode, based on their mobilities under conditions with suppressed EOF [85]. The analytes form boundaries and migrate towards the C 4 D detector.…”
Section: Simultaneous Determination Of Anions and Cationsmentioning
confidence: 99%
“…In another attempt, the separation of cations and anions was achieved by gradient elution moving boundary electrophoresis (GEMBE) [57]. GEMBE is a technique that involves electrophoretic separation in a short-length capillary using continuous injection against a variable In the capillary filling method, the separation capillary is filled with a sample containing anions and cations dissolved in BGE, and after a high voltage application, the anions and cations move to the appropriate electrode, based on their mobilities under conditions with suppressed EOF [85]. The analytes form boundaries and migrate towards the C 4 D detector.…”
Section: Simultaneous Determination Of Anions and Cationsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 They found that the number of shot signals was reduced and a broad peak of the dispersed graphene became narrower upon the addition of PEG and dodecylbenzenesulfonate in a separation buffer. Yamamoto et al reported on a concurrent analysis of inorganic anions and cations filled in a whole capillary in CE-C 4 D. 11 Under a suppressed EOF, the migrations of anions and cations to different polarities gave a stepwise electropherogram. Differentiation of the electropherogram resulted in a series of peaks of the ionic analytes.…”
mentioning
confidence: 99%
“…15 Takayanagi et al reported on the electrophoretic behavior of graphene, demonstrating that the dispersion of graphene in an aqueous solution can be monitored and that surfactant on the graphene surface is replaced competitively by water-soluble nonionic polymers. 16 CE and MCE can be connected with various detection methods [17][18][19][20] and analysis methods, such as mass spectrometry. This merit affords fruitful information about molecular species in a sample.…”
mentioning
confidence: 99%